SOCIAL CONFLICT IN PETER TIERYAS’S THE MECHA SAMURAI EMPIRE SERIES - Byvan Quai Alkana (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
This study discusses the social conflict in Peter Tieryas's Mecha Samurai Empire Series. The aim of the study is to find out the reason for the causes of social conflict and their effect in the three novels and to find out the categories and types of social conflicts that appear in the story. The writer chooses the novel series because of the depiction of social conflict in the post-World War two settings where Nazi Germany and the Empire of Japan win the second world war. In this study, the writer uses the qualitative descriptive method and sociological literature approach. To analyse the social conflicts of the novel series, the writer uses Ralf Dahrendorf's social conflict theory. The writer finds that there are two factors why social conflict appears in the novel, the background of the conflict and the attempt of each group in each novel to become the conflict group. Aside from that, the writer finds that the categories of conflict in the United States of Japan and Mecha Samurai Empire novel are exogenous conflict while Cyber Shogun Empire is endogenous conflict. There are four types of social conflict in the story. In the United States of Japan, the type of conflict is George Washingtons against the Empire of Japan. In Mecha Samurai Empire, the type of conflict is the National Revolutionaries of America against the Empire of Japan. In Cyber Shogun Revolution, there are two types of conflict, the Sons of War against the Empire of Japan and the Bloody Mary Group against the Empire of Japan.